Inverse Trigonometric Functions#0

Geometry Level 3

cot 1 ( 2 4 + 4 ) + cot 1 ( 6 4 + 4 ) + cot 1 ( 12 4 + 4 ) + = tan 1 ( p q ) \cot^{-1}\left(\frac 24 + 4\right) + \cot^{-1}\left(\frac 64 + 4\right) + \cot^{-1}\left(\frac {12}4 + 4\right) + \cdots = \tan^{-1}\left(\frac pq\right)

The equation above holds true for coprime positive integers p p and q q . Find p q p-q .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Feb 24, 2018

Let S n = k = 1 n cot 1 ( k ( k + 1 ) 4 + 4 ) = cot 1 a n \displaystyle S_n = \sum_{k=1}^n \cot^{-1} \left(\frac {k(k+1)}4+4\right) = \cot^{-1} a_n . From the first few a n a_n , we note that a n = n + 17 4 n a_n = \dfrac {n+17}{4n} . Let us prove in by induction that the claim is true for all n 1 n \ge 1 .

Proof: For n = 1 n=1 , a 1 = 1 + 17 4 ( 1 ) = 9 2 = 2 4 + 4 a_1 = \dfrac {1+17}{4(1)} = \dfrac 92 = \dfrac 24 + 4 as given. The claim is true for n = 1 n=1 . Assuming the claim is true for n n , then:

S n + 1 = S n + cot 1 ( ( n + 1 ) ( n + 2 ) 4 + 4 ) = cot 1 a n + cot 1 ( n 2 + 3 n + 18 4 ) = cot 1 ( n + 17 4 n ) + cot 1 ( n 2 + 3 n + 18 4 ) = cot 1 ( ( n + 17 4 n ) ( n 2 + 3 n + 18 4 ) 1 ( n + 17 4 n ) + ( n 2 + 3 n + 18 4 ) ) = cot 1 ( n 3 + 20 n 2 + 65 n + 306 4 ( n 3 + 3 n 2 + 19 n + 17 ) ) = cot 1 ( ( n + 18 ) ( n 2 + 2 n + 17 ) 4 ( n + 1 ) ( n 2 + 2 n + 17 ) ) = cot 1 ( n + 18 4 ( n + 1 ) ) \begin{aligned} S_{n+1} & = S_n + \cot^{-1} \left(\frac {(n+1)(n+2)}4 + 4 \right) \\ & = \cot^{-1} a_n + \cot^{-1} \left(\frac {n^2+3n+18}4 \right) \\ & = \cot^{-1} \left(\frac {n+17}{4n} \right) + \cot^{-1} \left(\frac {n^2+3n+18}4 \right) \\ & = \cot^{-1} \left(\frac {\left(\frac {n+17}{4n} \right)\left(\frac {n^2+3n+18}4 \right)-1} {\left(\frac {n+17}{4n} \right)+\left(\frac {n^2+3n+18}4 \right)}\right) \\ & = \cot^{-1} \left(\frac {n^3+20n^2+65n+306}{4(n^3+3n^2+19n+17)}\right) \\ & = \cot^{-1} \left(\frac {(n+18)(n^2+2n+17)}{4(n+1)(n^2+2n+17)}\right) \\ & = \cot^{-1} \left(\frac {n+18}{4(n+1)}\right) \end{aligned}

Therefore, the claim is also true for n + 1 n+1 and hence true for all n 1 n \ge 1 .

Now, we have lim n S n = lim n cot 1 ( n + 17 4 n ) = lim n cot 1 ( 1 + 17 n 4 ) = cot 1 ( 1 4 ) = tan 1 4 \displaystyle \lim_{n \to \infty} S_n = \lim_{n \to \infty} \cot^{-1} \left(\frac {n+17}{4n}\right) = \lim_{n \to \infty} \cot^{-1} \left(\frac {1+\frac {17}n}4 \right) = \cot^{-1} \left(\dfrac 14\right) = \tan^{-1} 4 .

Therefore, p q = 4 1 = 3 p-q = 4-1 = \boxed{3} .

Ashutosh Sharma
Feb 20, 2018

Aakhyat Singh
Feb 20, 2018

@Manu Sharma , could u pls explain how u solved this problem ?? Also(general doubt) how to solve such type of inverse+series problems ??

@Aakhyat Singh solution posted. Now coming to ur doubt, always try to frame terminating series(it will always be there atleast till where level of Iit is concerned) for ex. U could check the solution posted above.

Ashutosh Sharma - 3 years, 3 months ago

Log in to reply

Thanks @Manu Sharma .

Aakhyat Singh - 3 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...